2016
DOI: 10.3109/21691401.2016.1138495
|View full text |Cite
|
Sign up to set email alerts
|

Hepatogenic differentiation from human adipose-derived stem cells and application for mouse acute liver injury

Abstract: Adipose-derived stem cells (ADSCs) derived from adipose tissue have the capacity to differentiate into endodermal, mesoderm, and ectodermal cell lineages in vitro, which are an ideal engraft in tissue-engineered repair. In this study, human ADSCs were isolated from subcutaneous fat. The markers of ADSCs, CD13, CD71, CD73, CD90, CD105, CD166, CYP3A4, and ALB were detected by immunofluorescence assays. Human ADSCs were cultured in a specific hepatogenesis differentiation medium containing HGF, bFGF, nicotinamide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In addition, Zhou et al demonstrated that intravenous transplantation of hepatocyte-like cells from umbilical cord-derived MSCs into nude mice with CCl 4 -induced fulminant liver failure and acute liver injury not only improved serum parameters and the alternations of liver histology, but also improved survival rate of mice in severe hepatic failure [ 44 ]. There are also many other papers demonstrated that delivery of hepatocyte-like cells through intravenous injection was safe and effective [ 45 47 ]. To our knowledge, no attempts have so far been made to determine whether the hAESC-derived HLCs have the ability to improve liver function and rescue the acute hepatic failure mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Zhou et al demonstrated that intravenous transplantation of hepatocyte-like cells from umbilical cord-derived MSCs into nude mice with CCl 4 -induced fulminant liver failure and acute liver injury not only improved serum parameters and the alternations of liver histology, but also improved survival rate of mice in severe hepatic failure [ 44 ]. There are also many other papers demonstrated that delivery of hepatocyte-like cells through intravenous injection was safe and effective [ 45 47 ]. To our knowledge, no attempts have so far been made to determine whether the hAESC-derived HLCs have the ability to improve liver function and rescue the acute hepatic failure mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a debate concerning the use of ADMSCs and HLCs in vivo. As Guo et al demonstrated, transplantation of ADMSCs and HLCs improved liver function and rescued CCl 4 -treated mice with liver injury, but ADMSC transplantation improved liver functions more effectively than transplantation of HLCs [76]. HLCs significantly restored liver function and prolonged the survival of mice with CCl 4 -induced ALF by engraftment into the injured liver, but infusion of the liver with primary hepatocytes was not effective [66].…”
Section: Introductionmentioning
confidence: 99%
“…In other research, human ADSC-derived hepatocytes transplanted in a mouse model of liver fibrosis demonstrated improved serum levels of liver injury biochemical markers. However, non-differentiated ADSCs exhibited better results with a more accentuated decrease of ALT and AST three weeks after transplantation in comparison to ADSC-derived hepatocytes [143]. A divergent study showed that liver-injured rats who received ADSC-derived hepatocytes had better levels of serological markers (albumin, ALT, bilirubin, and alkaline phosphatase), increased levels of hepatic genes (albumin, alpha-fetoprotein, cytokeratin18, and HNF), and better cell homing than liver-injured rats who received undifferentiated ADSCs [141].…”
Section: Cell Types Used For the Inhibition Of Liver Fibrosismentioning
confidence: 99%